Cell-free supernatants from plant growth-promoting rhizobacteria Bacillus albus strains control Aspergillus flavus disease in peanut and maize seedlings - Lai Loi Trinh; Kim Ngoc Le; Hoang Anh Le Lam; Hoai Huong Nguyen (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Aspergillus flavus, a seed-borne fungal pathogen, colonizes host plants and exploits nutrients, hindering the growth of seedlings such as peanut and maize. This study investigates the effectiveness of cell-free supernatants (CFSs) from the plant growth-promoting rhizobacteria (PGPR) Bacillus albus strains NNK24 and NDP61, which belong to the Bacillus cereus group, in suppressing A. flavus AF1. Results The antifungal activity of these CFSs was attributed to their surfactant properties and chemical composition. These were characterized using rapid chemical assays and ultra-high-performance liquid chromatography-electrospray ionization-quadrupole time-of-flight/mass spectrometry (UHPLC-ESI-QTOF/MS), combined with bioinformatic tools such as Global Natural Product Social Molecular Networking (GNPS) and Natural Products Atlas (NPAtlas). Identified putative antifungal compounds included two diketopiperazines (cyclo(Pro-Leu) and cyclo(2-hydroxy-Pro-Leu)), four macrolactins (7-O-succinyl macrolactin A, 7-O-methyl-5′-hydroxy-3′-heptenoate-macrolactin, macrolactin B, and macrolactin C), two siderophores (petrobactin and bacillibactin), and three cyclic lipopeptides (kurstakin 1, 2 or 3, and 4). These compounds are hypothesized to act synergistically via multiple mechanisms, including disruption of fungal membranes, iron capture, direct antibiosis, and triggering plant immunity. Both CFSs strongly suppressed the harmful effects of A. flavus AF1 and seed-borne A. flavus on peanut and maize seedlings, reducing disease incidence (DI) and disease severity index (DSI) compared to controls. The disease control efficacy (DCE) of the CFSs was comparable to that of the commercial fungicide. Additionally, the CFSs enhanced seed germination, vigor, seedling length, and weight in both peanut and maize. Vigor index (VI) values increased by 222.4–286.0% in peanuts and 181.7–216.4% in maize at 7 days after treatment (DAT). Conclusion CFSs of B. albus NNK24 and NDP61 show significant potential as bioprotective agents for sustainable agriculture. Importantly, their use eliminates the need for live bacterial cells from the B. cereus group, addressing biosafety concerns. Graphical abstract